Kinetic Limitations in Single‐Crystal High‐Nickel Cathodes. Issue 32 (11th March 2021) - Ge, Mingyuan; Wi, Sungun; Liu, Xiang; Bai, Jianming; Ehrlich, Steven; Lu, Deyu; Lee, Wah‐Keat; Chen, Zonghai; Wang, Feng
Abstract: High‐nickel cathodes attract immense interest for use in lithium‐ion batteries to boost Li‐storage capacity while reducing cost. For overcoming the intergranular‐cracking issue in polycrystals, single‐crystals are considered an appealing alternative, but aggravating concerns on compromising the ionic transport and kinetic properties. We report here a quantitative assessment of redox reaction in single‐crystal LiNi0.8 Mn0.1 Co0.1 O2 using operando hard X‐ray microscopy/spectroscopy, revealing a strong dependence of redox kinetics on the state of charge (SOC). Specifically, the redox is sluggish at low SOC but increases rapidly as SOC increases, both in bulk electrodes and individual particles. The observation is corroborated by transport measurements and finite‐element simulation, indicating that the sluggish kinetics in single‐crystals is governed by ionic transport at low SOC and may be alleviated through synergistic interaction with polycrystals integrated into a same electrode. Abstract : By X‐ray spectromicroscopy of electrochemical reaction in single‐crystal LiNi0.8 Mn0.1 Co0.1 O2 coupled with finite element simulation, we reveal strong dependence of redox kinetics on the state of charge (SOC). Specifically, the redox reaction is sluggish at low SOC, but increases rapidly as SOC increases. The kinetic limitation at low SOC can be alleviated through interaction with polycrystals integrated into the same electrode.